Obraz mityczny jako obraz kulturowy = Mythical Image as Culture Image - Kwiatkowska, Ewa (Studia religiologica, 2013)
The article presents the idea of the active image in culture connected with the approach to image cultures as reservoirs and ways of constructing collective imagination spheres. This view makes it possible to present the issue of mythical image as a particular kind of cultural image. The mythical image in the context of the traditions of Warburg and Benjamin may be recognised thanks to its actions in culture characteristic of mythical expressions. The second part of the article deals with the premises of the iconological use of Walter Benjamin’s reflections in the context of his concept of the myth and dialectical image